REPRESENTATION OF THE TIME CATEGORY IN THE LINGUISTIC BASIS. - Boltakulova Gulnoza Farrukhovna (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract. The article investigates the cognitive means of the temporal categories. It examines how individuals conceptualize and interpret time in their respective languages. Furthermore, this article analyzes temporal expressions in both English and Uzbek languages, identifying similarities and differences in how time is represented linguistically.